Aerogel composite material, heat-resistant pad containing the same, and method for manufacturing a heat-resistant pad
Patent Information
- Application Number
- JP2026522082
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-06-26
- Filing Date
- 2025-06-27
- Publication Date
- 2026-10-30
AI Technical Summary
【0029】 本発明は、乾式でエアロゲル複合材を含む断熱層を製造し、価格競争力が高くて工程効率の高い耐熱パッドの製造方法を提供することができる。
Smart Images

Figure 2026536512000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2024-0086361 filed on July 1, 2024 and Korean Patent Application No. 10-2025-0085474 filed on June 26, 2025, and all contents disclosed in the documents of the said Korean patent applications are incorporated as part of the present specification.
[0002] The present invention relates to an aerogel composite material, a heat-resistant pad comprising the same, and a method for manufacturing the heat-resistant pad, and more specifically, to a method for manufacturing a heat-resistant pad including a method for dry-manufacturing a heat-resistant pad containing aerogel. BACKGROUND ART
[0003] As technological development and demand for mobile devices increase, the demand for secondary batteries as an energy source is rapidly increasing. In particular, secondary batteries have drawn great attention as an energy source not only for mobile devices such as mobile phones, digital cameras, laptop computers, and wearable devices, but also for power units such as electric bicycles, electric vehicles, and hybrid electric vehicles.
[0004] A battery cell of a secondary battery is manufactured by embedding an electrode assembly together with an electrolyte in a secondary battery case, and the electrode assembly is manufactured by laminating and / or winding a positive electrode, a separator, and a negative electrode. A plurality of the manufactured battery cells are stacked to constitute a battery module or a battery pack.
[0005] When heat may be generated in the battery cells due to the operation of the cells, and the heat is transferred to and accumulated in adjacent battery cells, battery thermal runaway (Thermal Propagation) occurs.
[0006] To prevent such problems, much research is being conducted on preventing fires inside battery packs by placing heat-resistant pads between battery cells. In particular, research continues on heat-resistant pads that are both highly heat-resistant and easy to manufacture. [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] The present invention aims to solve the aforementioned problems and provides a method for manufacturing a heat insulating layer containing an aerogel composite material by a dry process, and a method for manufacturing a heat-resistant pad containing the same.
[0008] Furthermore, the present invention aims to provide an aerogel composite material and a heat-resistant pad including an insulating layer containing the same. [Means for solving the problem]
[0009] The present invention provides a method for manufacturing a heat-resistant pad, comprising the steps of: mixing a fluororesin and aerogel particles in a solid state in a weight ratio of 1:1 or more and 1:1.5 or less to form an aerogel composite material; and forming the aerogel composite material into a sheet to form a heat insulating layer.
[0010] In one embodiment, the step of forming the aerogel composite material may be carried out in a single step.
[0011] In one embodiment, the step of forming the aerogel composite material may include a first step of mixing ceramic particles and the fluororesin in a solid form to form a precursor; and a second step of mixing the precursor and the aerogel particles in a solid form to form the aerogel composite material.
[0012] In one embodiment, the mixed weight ratio of the ceramic particles and the fluororesin in the first step may be 2:1 or more and 9:1 or less.
[0013] In one embodiment, the first step may be a step of mixing the ceramic particles and the fluororesin while applying shear stress.
[0014] In one embodiment, the second step may be a step of kneading and mixing the precursor and the aerogel particles.
[0015] In one embodiment, the ceramic particles may include one or more selected from the group consisting of silicon oxide, zirconium oxide, yttrium oxide, aluminum oxide (Al2O3), boehmite, aluminum trihydrate, calcium oxide, phosphate oxide, phosphorus pentoxide (P2O5), glass fiber, glass bubble, and chopped glass.
[0016] In one embodiment, the fluororesin may include one or more selected from the group consisting of polytetrafluoroethylene (PTFE) resin, polyfluoroalkoxy (PFA) resin, and polyvinylidene fluoride (PVDF) resin.
[0017] In one embodiment, the aerogel particles may include silica aerogel particles.
[0018] In one embodiment, the aerogel composite material may be formed into a sheet by pressing the aerogel composite material.
[0019] In one embodiment, the thermal conductivity of the insulating layer may be 0.02 W / m·K or more and 0.1 W / m·K or less.
[0020] In one embodiment, the process further includes the step of forming a support layer on at least one surface of the heat insulating layer, the support layer may include one or more selected from the group consisting of silicone-based resin, aramid fiber, spun yarn, mica pad, and mica paper.
[0021] In one embodiment, the silicone-based resin may be silicone rubber.
[0022] The aerogel composite material of the present invention contains a fluorine-based resin and aerogel particles at a weight ratio of 1:1 to 1:1.5.
[0023] In one embodiment, the aerogel particles may include silica aerogel particles.
[0024] In one embodiment, the fluorine-based resin may include one or more selected from the group consisting of polytetrafluoroethylene (PTFE) resin, polyfluoroalkoxy (PFA) resin, and polyvinylidene fluoride (PVDF) resin.
[0025] In one embodiment, the aerogel composite material may further include ceramic particles.
[0026] In one embodiment, the mixing weight ratio of the ceramic particles to the fluorine-based resin may be 2:1 to 9:1.
[0027] In one embodiment, the ceramic particles may include one or more selected from the group consisting of silicon oxide, zirconium-based oxides, yttrium-based oxides, aluminum oxide (Al2O3), boehmite, aluminum trihydrate, calcium oxide, phosphoric acid-based oxides, phosphorus pentoxide (P2O5), glass fiber, glass bubble, and chopped glass.
[0028] The heat-resistant pad of the present invention includes a heat insulating layer containing the aerogel composite material.
Effects of the Invention
[0029] This invention provides a method for manufacturing a heat-resistant pad that is highly competitive in price and has high process efficiency, by producing a heat-insulating layer containing an aerogel composite material using a dry process.
[0030] Furthermore, the present invention can provide an aerogel composite material manufactured by the above method and a heat-resistant pad containing the same. [Brief explanation of the drawing]
[0031] [Figure 1] This is a photograph of the aerogel composite material manufactured in Example 1. [Figure 2] This is an SEM image of the aerogel composite material manufactured in Example 1. [Figure 3] This is an SEM image of the aerogel composite material manufactured in Example 1. [Figure 4] This is a photograph of the aerogel composite material manufactured in Example 2. [Figure 5] This is an SEM image of the aerogel composite material manufactured in Example 2. [Figure 6] This is an SEM image of the aerogel composite material manufactured in Example 2. [Figure 7] This is an SEM image of the aerogel composite material manufactured in Example 3. [Figure 8] This is an SEM image of the aerogel composite material manufactured in Example 3. [Figure 9] This is an image of the insulation layer manufactured in Example 3. [Figure 10] This is an image of the heat-resistant pad manufactured in Example 3. [Figure 11] This is an SEM image of the mixture of fluororesin and aerogel particles produced in Comparative Example 1. [Figure 12] This is an image of the mixture of ceramic particles, fluororesin, and aerogel particles produced in Comparative Example 2. [Figure 13] This is an image of the mixture of ceramic particles, fluororesin, and aerogel particles produced in Comparative Example 3. [Figure 14]Figure 13 is an SEM image of the mixture. [Figure 15] This is an image of the mixture of ceramic particles, fluororesin, and aerogel particles produced in Comparative Example 4. [Figure 16] Figure 15 is an SEM image of the mixture. [Figure 17] This is an image of the mixture of fluororesin and aerogel particles produced in Comparative Example 5. [Modes for carrying out the invention]
[0032] The following describes various embodiments of the present invention in detail, with reference to the attached drawings, so that those with ordinary skill in the art to which the present invention pertains can easily implement them. The present invention can be embodied in a variety of different forms and is not limited to the embodiments described herein.
[0033] To clearly explain the present invention, unnecessary explanatory parts have been omitted, and the same or similar reference numerals are used throughout the specification for identical or similar components.
[0034] Furthermore, the dimensions and thicknesses of each component shown in the drawings are arbitrary for illustrative purposes and are not necessarily limited to those shown in the present invention. Thicknesses are shown enlarged in the drawings to clearly represent multiple layers and regions. Additionally, the thicknesses of some layers and regions are exaggerated in the drawings for illustrative purposes.
[0035] Furthermore, when we say that a layer, membrane, region, plate, or other part is "on top of" another part, this includes not only the case where it is "directly above" the other part, but also the case where the other part is in between. When one part is "directly above" another part, it means that there is no other part in between. Also, being "on top of" a reference part means being located above or below the reference part, and does not necessarily mean being located "up" in the opposite direction of gravity.
[0036] Furthermore, when a specification states that a certain part "includes" a certain component, unless otherwise stated, this does not mean that other components are excluded, but rather that other components may be included.
[0037] The following describes the aerogel composite material of the present invention, a heat-resistant pad containing the same, and a method for manufacturing the heat-resistant pad.
[0038] The method for manufacturing the heat-resistant pad of the present invention is as follows: A step of mixing a fluororesin and aerogel particles in a solid state in a weight ratio of 1:1 or more and 1:1.5 or less to form an aerogel composite material; and The process includes the step of forming a thermal insulation layer by forming the aerogel composite material into a sheet;
[0039] The present invention relates to a method for manufacturing a heat-resistant pad that includes an insulating layer, and the heat-resistant pad manufactured by the method of the present invention may include only the insulating layer, or may further include a support layer disposed on at least one surface of the insulating layer. Examples of such a heat-resistant pad manufacturing method will be described in detail below.
[0040] One embodiment of the method for manufacturing a heat-resistant pad includes the steps of mixing a fluororesin and aerogel particles in a solid state in a weight ratio of 1:1 or more and 1:1.5 or less to form an aerogel composite material, and forming the aerogel composite material into a sheet to form a heat insulating layer.
[0041] In one embodiment, the step of forming the aerogel composite material may be carried out in a single step (one-step). That is, the step of forming the aerogel composite material may be a step of mixing powdered fluororesin and aerogel particles in a solid form.
[0042] The mixing may be carried out using equipment capable of applying shear stress, such as a household blender.
[0043] In one embodiment, the fluororesin may include one or more selected from the group consisting of polytetrafluoroethylene (PTFE) resin, polyfluoroalkoxy (PFA) resin, and polyvinylidene fluoride (PVDF) resin. For example, polytetrafluoroethylene (PTFE) resin may be used as the fluororesin, but the examples are not limited thereto.
[0044] In one embodiment, the aerogel particles may be inorganic aerogel particles, and specifically, silica aerogel particles. The aerogel particles have excellent heat insulation properties and are used as the main component for manufacturing a heat insulating layer.
[0045] The fluororesin and aerogel particles are supplied in powder form and mixed in a solid state. In other words, the fluororesin and aerogel particles are mixed dry without a separate solvent.
[0046] Generally, the wet manufacturing process for aerogel composites is costly because it takes about 1 to 3 days to grow the aerogel precursor on the surface of a support such as glass fiber, and then requires a process to selectively remove the solvent from the aerogel precursor using methods such as supercritical fluid or room temperature pressurization. In contrast, the present invention forms an aerogel composite by mixing a fluororesin and aerogel particles in a dry process, so the process time is less than 10 minutes, and it has the advantage of being a simpler process than the wet manufacturing process, resulting in relatively shorter time and costs.
[0047] The fluororesin and aerogel particles may be mixed in a weight ratio of 1:1 to 1:1.5. If the amount of aerogel particles decreases and the weight ratio of fluororesin to aerogel particles (fluororesin weight: aerogel particle weight) falls below 1:1, it may be difficult to form a pad of the aerogel composite material, or even if it is possible to manufacture the aerogel composite material and the insulation layer, the manufactured insulation layer may not provide sufficient insulation. If the amount of aerogel particles increases and the weight ratio of fluororesin to aerogel particles (fluororesin weight: aerogel particle weight) exceeds 1:1.5, the amount of fluororesin that acts as a web connecting the aerogel particles decreases relatively, making it difficult to form a pad of the aerogel composite material. In other words, it becomes difficult to manufacture the insulation layer.
[0048] In this invention, a dry manufacturing method for aerogel composite material is provided, by mixing a fluororesin and aerogel particles in a solid form in a weight ratio of 1:1 to 1:1.5, thereby providing an aerogel composite material that is highly price-competitive, has excellent heat insulation properties, and is easy to form into pads.
[0049] The aerogel composite material formed as described above may be manufactured by forming it into a sheet and creating an insulating layer. Forming the aerogel composite material into a sheet is a step of pressing the aerogel composite material into a sheet shape. The pressing may be carried out by known methods such as calendering.
[0050] In one embodiment, if the step of forming the aerogel composite material is performed in a single step, it may include the steps of mixing fluororesin and aerogel particles in a solid form in a weight ratio of 1:1 or more and 1:1.5 or less, without any other components other than the fluororesin and aerogel particles, and forming the aerogel composite material into a sheet to form a heat insulating layer.
[0051] In another embodiment, the step of forming the aerogel composite material may be carried out in two or more steps, for example, in two steps.
[0052] In one embodiment, the step of forming the aerogel composite material may include a first step of mixing ceramic particles and the fluororesin in a solid state to form a precursor, and a second step of mixing the precursor and aerogel particles in a solid state to form the aerogel composite material.
[0053] The first step is to mix the ceramic particles and the fluororesin, which are in powder form, in a solid state to form a precursor.
[0054] The first step is a process for fiberizing the fluororesin. By mixing ceramic particles with the fluororesin, the fiberization of the fluororesin can be more easily induced. The first step may be carried out using equipment capable of applying shear stress, such as a household blender. The mixing of the ceramic particles and the fluororesin is carried out without a separate solvent, i.e., dry. Therefore, the process time is short and the cost is relatively low.
[0055] In this embodiment, the ceramic particles and the fluororesin may be mixed in a weight ratio of ceramic particles to fluororesin of 2:1 or more and 9:1 or less. When the above ratio is satisfied, the fluororesin can be easily formed into fibers.
[0056] In one embodiment, the ceramic particles may include one or more selected from the group consisting of silicon oxide, zirconium oxide, yttrium oxide, aluminum oxide (Al2O3), boehmite, aluminum trihydrate, calcium oxide, phosphate oxide, phosphorus pentoxide (P2O5), glass fiber, glass bubbles, and chopped glass. For example, milled glass fiber processed with ceramic particles, chopped glass, silicon oxide, zirconium oxide, or aluminum oxide can be used, and more specifically, a mixture of milled glass fiber and chopped glass may be used, but the examples are not limited thereto.
[0057] The same explanations as above apply to fluoropolymer resins.
[0058] The second step is to mix aerogel particles in a solid form with the precursor formed in the first step to form an aerogel composite. The description of the aerogel particles is the same as described above.
[0059] The mixing of the precursor and aerogel particles is performed dryly without the need for a separate solvent. Therefore, the process time is short and the cost is relatively low.
[0060] When mixing the precursor and aerogel particles, the mixing may be based on the weight ratio of the fluororesin to the aerogel particles contained in the precursor. In other words, the precursor and aerogel particles are mixed so that the weight ratio of the fluororesin to aerogel particles contained in the precursor is between 1:1 and 1:1.5. When this ratio is satisfied, the fluororesin can be easily formed into fibers.
[0061] The second step may be a step of kneading the precursor and aerogel particles produced in the first step. For example, the process of kneading the precursor and aerogel particles may be carried out using a PD mixer (Planetary disperser mixer) or a twin screw extruder.
[0062] In this embodiment, when the first and second steps are performed in a single step, that is, when the ceramic particles, fluororesin, and aerogel particles are mixed simultaneously in solid form, there is a possibility that the aerogel particles may crack. Such particle cracking may increase the specific surface area of the aerogel particles and reduce the relative proportion of fluororesin that can cover the surface of the aerogel particles, potentially preventing the aerogel composite from forming a pad.
[0063] Therefore, when adding ceramic particles, the aerogel composite material can be formed in two steps, as described above, and then a thermal insulation layer can be formed by sheeting the aerogel composite material. The sheeting of the aerogel composite material may be carried out by a press method as described above.
[0064] The present invention provides a method for manufacturing a heat-resistant pad, which involves mixing a fluororesin, aerogel particles, and selectively ceramic particles in solid form to form an aerogel composite material, and then forming the aerogel composite material into a sheet to produce a heat insulating layer.
[0065] The thermal conductivity of the manufactured insulation layer may be 0.02 W / m·K or more and 0.1 W / m·K or less. The insulation layer of the present invention, by containing aerogel particles, has excellent heat resistance and can be manufactured by a dry process, reducing process time and cost compared to a wet process.
[0066] On the other hand, the method for manufacturing a heat-resistant pad according to one embodiment may also provide a method for manufacturing an insulating layer. In other words, a heat-resistant pad manufactured by the method for manufacturing a heat-resistant pad according to one embodiment may also provide the aforementioned insulating layer.
[0067] Another embodiment of the present invention's method for manufacturing a heat-resistant pad may include the steps of forming an insulating layer and forming a support layer. In other words, a heat-resistant pad manufactured by the method according to one embodiment may include an insulating layer and a support layer disposed on at least one surface of the insulating layer.
[0068] The step of forming the insulation layer is the same as the manufacturing method for the insulation layer described above. In other words, the step of forming the insulation layer is carried out in the step of forming the aerogel composite material in one or two steps, as described above, and the step of forming the insulation layer by sheeting the aerogel composite material. A detailed explanation of this is omitted.
[0069] The step of forming the support layer is to form the support layer on at least one surface of the thermal insulation layer. For example, the support layer may be formed on both sides of the thermal insulation layer, but the embodiments are not limited thereto.
[0070] The support layer may include a heat-resistant material. Specifically, the support layer may include one or more selected from the group consisting of silicone-based resin, fabric, and ceramic material. For example, silicone rubber can be used as the silicone-based resin. For example, aramid fibers or spun yarn can be used as the fabric. For example, mica pads or mica paper can be used as the ceramic material. In other words, the support layer may include one or more selected from the group consisting of silicone-based resin, aramid fibers, spun yarn, mica pads, and mica paper.
[0071] In one embodiment, the support layer may be made of silicone rubber. In this case, the support layer may be formed by applying and curing a silicone rubber solution to at least one surface of the heat insulating layer. However, the embodiment of the support layer is not limited thereto.
[0072] In one embodiment, the support layer may further include one or more selected from the group consisting of fabric or ceramic material, with silicone rubber as the adhesive layer. In this case, the steps may be to apply the silicone rubber solution to at least one surface of the heat insulating layer, adhere the fabric or ceramic material onto the silicone rubber solution, and then cure the silicone rubber solution to form the support layer.
[0073] One embodiment of the method for manufacturing a heat-resistant pad can provide a method for providing a heat-resistant pad that includes an insulating layer and a support layer. As a result, the provided heat-resistant pad can have further improved strength and flexibility. Such a heat-resistant pad can be placed, for example, between battery cells to prevent heat generated in one battery cell from being transferred and accumulated in an adjacent battery cell, thereby preventing thermal propagation.
[0074] The aerogel composite material of the present invention is It contains fluororesin and aerogel particles in a weight ratio of 1:1 to 1:1.5.
[0075] In one embodiment, the aerogel composite material may be manufactured by the step of forming the aerogel composite material in the heat-resistant pad manufacturing method described above. That is, the aerogel composite material in one embodiment may be formed by mixing a fluororesin and aerogel particles in a solid form in a weight ratio of 1:1 or more and 1:1.5 or less. Therefore, the detailed description of the fluororesin and aerogel particles in the aerogel composite material of the present invention is similar to that described above.
[0076] In one embodiment, the aerogel particles may include silica aerogel particles.
[0077] In one example, the fluororesin may include one or more selected from the group consisting of polytetrafluoroethylene (PTFE) resin, polyfluoroalkoxy (PFA) resin, and polyvinylidene fluoride (PVDF) resin.
[0078] In one embodiment, the aerogel composite may further contain ceramic particles to more easily induce the fiber formation of the fluororesin. That is, the aerogel composite of one embodiment may be formed by a first step of mixing the ceramic particles and the fluororesin in a solid form to form a precursor, and a second step of mixing the precursor and the aerogel particles in a solid form to form the aerogel composite. Accordingly, the above description applies similarly to the detailed explanation of the ceramic particles in the aerogel composite of the present invention.
[0079] In one embodiment, the mixed weight ratio of ceramic particles and fluororesin may be 2:1 or more and 9:1 or less. In another embodiment, the ceramic particles may include one or more selected from the group consisting of silicon dioxide, zirconium oxide, yttrium oxide, aluminum oxide (Al2O3), boehmite, aluminum trihydrate, calcium oxide, phosphate oxide, phosphorus pentoxide (P2O5), glass fiber, glass bubble, and chopped glass.
[0080] The aerogel composite material of the present invention contains a fluororesin and aerogel particles in a weight ratio of 1:1 to 1:1.5, thereby exhibiting excellent heat insulation properties, easy sheet formation, and superior processability.
[0081] The heat-resistant pad of the present invention is Includes an insulating layer containing the aerogel composite material.
[0082] In one embodiment, the heat-resistant pad includes an insulating layer containing the aerogel composite material described above. Specifically, the insulating layer may be formed by forming the aerogel composite material into a sheet. The method for forming the sheet can be similarly applied to the step of forming the insulating layer by forming the aerogel composite material into a sheet in the heat-resistant pad manufacturing method described above.
[0083] In one embodiment, the heat-resistant pad of the present invention may include an insulating layer and a support layer disposed on at least one surface of the insulating layer. A detailed description of the support layer is similarly provided above.
[0084] The heat-resistant pad of the present invention can exhibit excellent heat resistance by including an insulating layer containing an aerogel composite material. Furthermore, the heat-resistant pad of the present invention can improve flexibility by including a support layer in the insulating layer.
[0085] Hereinafter, embodiments of the present invention will be described in detail so that they can be easily implemented by a person with ordinary skill in the art to which the present invention pertains. However, the present invention can be embodied in a variety of different forms and is not limited to the embodiments described herein.
[0086] <Example 1> A fluororesin and aerogel particles were mixed in a 1:1 weight ratio in solid form to form an aerogel composite material. PTFE was used as the fluororesin, and silica aerogel particles were used as the aerogel particles. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0087] Figure 1 is a photograph of the aerogel composite material produced in Example 1. Figures 2 and 3 are SEM images of the aerogel composite material produced in Example 1. Referring to Figures 1 to 3, it can be confirmed that the fluororesin was adsorbed onto the surface of the aerogel particles, and that the aerogel particles were uniformly bonded to each other by the fluororesin.
[0088] <Example 2> A fluororesin and aerogel particles were mixed in a solid state at a weight ratio of 1:1.5 to form an aerogel composite material. PTFE was used as the fluororesin, and silica aerogel particles were used as the aerogel particles. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0089] Figure 4 is a photograph of the aerogel composite material produced in Example 2. Figures 5 and 6 are SEM images of the aerogel composite material produced in Example 2.
[0090] Referring to Figures 4 to 6, it can be confirmed that the aerogel particles are linked and bonded together by the adsorption of fluororesin onto their surfaces.
[0091] <Example 3> A precursor was formed by mixing ceramic particles and a fluororesin in a solid state at a weight ratio of 2:1. Aluminum oxide (Al2O3) was used as the ceramic particles, and PTFE was used as the fluororesin. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0092] The precursor thus formed was mixed in solid form with aerogel particles to form an aerogel composite material. At this time, the aerogel particles were mixed with the fluororesin contained in the precursor in a 1:1 weight ratio. Silica aerogel particles were used as the aerogel particles. Mixing was performed using a Primix Hivis Mix (planetary mixer) at 45 rpm for 45 minutes.
[0093] Figures 7 and 8 are SEM images of the aerogel composite material produced in Example 3. Referring to Figures 7 and 8, it can be seen that a precursor, which is a mixture of ceramic particles and a fluororesin, is present in a network-like structure covering the aerogel.
[0094] Subsequently, the formed aerogel composite material was pressed into a sheet using QMESYS's automatic air heating hot press (Air heating plating test, QM940AS model) to form an insulating layer. Figure 9 shows an image of the insulating layer manufactured in Example 3. Referring to Figure 9, it can be confirmed that the insulating layer has a sheet shape.
[0095] Subsequently, a support layer was formed by spraying a silicone rubber solution onto both sides of the formed insulation layer and then heat-curing it. The silicone rubber solution used was a mixture of PDMS (polydimethylsiloxane), a crosslinking agent, and a platinum (Pt) catalyst in a weight ratio of PDMS:crosslinking agent:platinum catalyst = 100:1:1. Heat curing was carried out in an 80°C oven for 10 minutes. Through this process, a heat-resistant pad including the insulation layer and the support layer was manufactured. Figure 10 is an image of the heat-resistant pad manufactured in Example 3. Referring to Figure 10, it can be seen that the heat-resistant pad can be bent in one direction due to the inclusion of the support layer. In other words, it can be seen that the flexibility of the heat-resistant pad is further enhanced by the inclusion of the support layer.
[0096] <Comparative Example 1> We attempted to form an aerogel composite material by mixing a fluororesin and aerogel particles in a solid state at a weight ratio of 1:5. PTFE was used as the fluororesin, and silica aerogel particles were used as the aerogel particles. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0097] Figure 11 is an SEM image of the mixture of fluororesin and aerogel particles produced in Comparative Example 1. As shown in Figure 11, in Comparative Example 1, the fluororesin and aerogel were not mixed, and no aerogel composite material was formed. This is presumably because the amount of fluororesin per unit volume was smaller compared to Examples 1 and 2, making it difficult to form a web through fiberization.
[0098] Because the aerogel composite material was not formed, it was impossible to manufacture the heat-insulating layer, and therefore impossible to manufacture the heat-resistant pad.
[0099] <Comparative Example 2> Ceramic particles, fluororesin, and aerogel particles were mixed in a solid state in a weight ratio of 2:1:4, and the mixing was performed simultaneously in a single step. Aluminum oxide (Al2O3) was used as the ceramic particles, PTFE as the fluororesin, and silica aerogel particles as the aerogel particles.
[0100] The mixture was blended using a household blender at 3500 rpm for 15 minutes.
[0101] Figure 12 shows an image of the mixture of ceramic particles, fluororesin, and aerogel particles produced in Comparative Example 2.
[0102] Referring to Figure 12, the mixture was not padded, and SEM analysis was impossible due to dust.
[0103] <Comparative Example 3> A precursor was formed by mixing ceramic particles and a fluororesin in a solid state at a weight ratio of 1:1. Aluminum oxide (Al2O3) was used as the ceramic particles, and PTFE was used as the fluororesin. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0104] The precursor thus formed was mixed in solid form with aerogel particles to form an aerogel composite material. At this time, the aerogel particles were mixed in at a weight four times that of the fluororesin contained in the precursor. Silica aerogel particles were used as the aerogel particles. Mixing was performed using a Primix Hivis Mix (planetary mixer) at 45 rpm for 45 minutes.
[0105] Figure 13 is an image of the mixture of ceramic particles, fluororesin, and aerogel particles produced in Comparative Example 3. Figure 14 is an SEM image of the mixture in Figure 13.
[0106] Referring to Figure 13, it can be seen that no aerogel composite material is formed, and the mixture exists in powder form. Referring to Figure 14, it can be seen that because the ratio of aerogel particles is relatively high compared to the precursor, only a portion of the aerogel particles form a composite with the precursor, and there are more aerogel particles that do not form a composite with the precursor.
[0107] <Comparative Example 4> A precursor was formed by mixing ceramic particles and a fluororesin in a solid state at a weight ratio of 10:1. Aluminum oxide (Al2O3) was used as the ceramic particles, and PTFE was used as the fluororesin. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0108] The precursor thus formed was mixed in solid form with aerogel particles to form an aerogel composite material. At this time, the aerogel particles were mixed in at a weight four times that of the fluororesin contained in the precursor. Silica aerogel particles were used as the aerogel particles. Mixing was performed using a Primix Hivis Mix (planetary mixer) at 45 rpm for 45 minutes.
[0109] Figure 15 is an image of the mixture of ceramic particles, fluororesin, and aerogel particles produced in Comparative Example 4. Figure 16 is an SEM image of the mixture in Figure 15.
[0110] Referring to Figure 15, it can be seen that no aerogel composite material was formed, and the mixture existed in powder form. Furthermore, referring to Figure 16, it can be seen that, due to the very high proportion of ceramic particles, the ceramic particles are densely distributed within the aerogel composite material, and some are aggregated. The aerogel particles are partially present between the ceramic particles, and it can be seen that sufficient bonding has not been formed between the precursor and the aerogel particles.
[0111] <Comparative Example 5> A fluororesin and aerogel particles were mixed in a solid state at a weight ratio of 2:1 to form an aerogel composite material. PTFE was used as the fluororesin, and silica aerogel particles were used as the aerogel particles. Mixing was performed using a household blender at 3500 rpm for 15 minutes.
[0112] Figure 17 shows an image of the mixture of fluororesin and aerogel particles produced in Comparative Example 5.
[0113] Referring to Figure 17, aggregates of fluororesin were found in the circular area, and it can be confirmed that multiple such aggregates were formed, indicating that the fluororesin and aerogel were not mixed. Because the aerogel composite material was not formed, it was impossible to manufacture the heat-insulating layer and thus the heat-resistant pad.
[0114] Referring to Examples 1 and 2, Comparative Examples 1, 2 and 5, it was confirmed that by adjusting the weight ratio of the fluororesin and aerogel particles to 1:1 or more and 1:1.5 or less when mixing them in a solid state, a uniform web is formed between the fluororesin and aerogel particles, making it possible to form a pad.
[0115] Furthermore, referring to Example 3, Comparative Example 3, and Comparative Example 4, it was confirmed that even when ceramic particles, fluororesin, and aerogel particles are mixed in two steps, if the weight ratio of ceramic particles, fluororesin, and aerogel particles exceeds the range of the present invention, it is difficult to form an aerogel composite material and difficult to form a pad.
[0116] Referring to Examples 1 to 3, the present invention provides a method for manufacturing a heat-resistant pad, which involves mixing a fluororesin, aerogel particles, and selectively ceramic particles in solid form, mixing the fluororesin and aerogel particles in a weight ratio of 1:1 to 1:1.5 to form an aerogel composite material, and forming the aerogel composite material into a sheet to form a heat insulating layer.
[0117] The heat-resistant pad manufacturing method of the present invention is performed dry, offering excellent processability, and the heat-resistant pad manufactured by this method can have excellent heat insulation properties. Furthermore, one embodiment of the present invention provides a heat-resistant pad with further improved strength and flexibility by further including the step of forming a support layer on the heat-insulating layer.
[0118] Although preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto. Various modifications and improvements of the basic concepts of the present invention, as defined in the following claims, also fall within the scope of the present invention.
Claims
1. A step of mixing a fluororesin and aerogel particles in a solid state in a weight ratio of 1:1 or more and 1:1.5 or less to form an aerogel composite material; and A method for manufacturing a heat-resistant pad, comprising the step of forming the aerogel composite material into a sheet to form an insulating layer.
2. The method for manufacturing a heat-resistant pad according to claim 1, wherein the step of forming the aerogel composite material is carried out in a single step.
3. The step of forming the aerogel composite material is: A first step of mixing ceramic particles and the fluororesin in a solid state to form a precursor; and A method for manufacturing a heat-resistant pad according to claim 1, comprising a second step of mixing the precursor and the aerogel particles in a solid state to form the aerogel composite material.
4. The method for manufacturing a heat-resistant pad according to claim 3, wherein in the first step, the mixed weight ratio of the ceramic particles and the fluororesin is 2:1 or more and 9:1 or less.
5. The method for manufacturing a heat-resistant pad according to claim 3, wherein the first step is to mix the ceramic particles and the fluororesin by applying shear stress.
6. The method for manufacturing a heat-resistant pad according to claim 3, wherein the second step is to knead and mix the precursor and the aerogel particles.
7. The ceramic particles include silicon dioxide, zirconium oxide, yttrium oxide, and aluminum oxide (Al 2 O 3 ), boehmite, aluminum trihydrate, calcium oxide, phosphate oxides, phosphorus pentoxide (P 2 O 5 A method for manufacturing a heat-resistant pad according to claim 3, comprising one or more selected from the group consisting of Phosphorus pentoxide, glass fiber, glass bubble, and chopped glass.
8. The method for producing a heat-resistant pad according to any one of claims 1 to 7, wherein the fluororesin comprises one or more selected from the group consisting of polytetrafluoroethylene (PTFE) resin, polyfluoroalkoxy (PFA) resin, and polyvinylidene fluoride (PVDF) resin.
9. The method for manufacturing a heat-resistant pad according to any one of claims 1 to 7, wherein the aerogel particles include silica aerogel particles.
10. The method for manufacturing a heat-resistant pad according to any one of claims 1 to 7, wherein the aerogel composite material is formed into a sheet by pressing the aerogel composite material.
11. A method for manufacturing a heat-resistant pad according to any one of claims 1 to 7, wherein the thermal conductivity of the heat-insulating layer is 0.02 W / m·K or more and 0.1 W / m·K or less.
12. The step further includes forming a support layer on at least one surface of the thermal insulation layer, A method for manufacturing a heat-resistant pad according to any one of claims 1 to 7, wherein the support layer comprises one or more selected from the group consisting of silicone-based resin, aramid fiber, spun yarn, mica pad, and mica paper.
13. The method for manufacturing a heat-resistant pad according to claim 12, wherein the silicone resin is silicone rubber.
14. An aerogel composite material containing fluororesin and aerogel particles in a weight ratio of 1:1 to 1:1.
5.
15. The aerogel composite material according to claim 14, wherein the aerogel particles include silica aerogel particles.
16. The aerogel composite material according to claim 14 or 15, wherein the fluororesin comprises one or more selected from the group consisting of polytetrafluoroethylene (PTFE) resin, polyfluoroalkoxy (PFA) resin, and polyvinylidene fluoride (PVDF) resin.
17. The aerogel composite material according to claim 14 or 15, further comprising ceramic particles.
18. The aerogel composite material according to claim 17, wherein the mixed weight ratio of the ceramic particles and the fluororesin is 2:1 or more and 9:1 or less.
19. The ceramic particles include silicon dioxide, zirconium oxide, yttrium oxide, and aluminum oxide (Al 2 O 3 ), boehmite, aluminum trihydrate, calcium oxide, phosphate oxides, phosphorus pentoxide (P 2 O 5 The aerogel composite material according to claim 17, comprising one or more selected from the group consisting of Phosphorus pentoxide, glass fiber, glass bubble, and chopped glass.
20. A heat-resistant pad comprising a heat insulating layer containing the aerogel composite material according to claim 14 or 15.